Markowitz and Sharpe’s Approaches to Portfolio Construction â€“ A Comparison in Indian Context - Mehta, Sushil Kumar (Indian Journal of Finance, 2008)
The study was conducted to compare the Ex-ante performance of portfolios constructed using Mean-Variance Model of Markowitz and Single Index Model of Sharpe. Weekly data was collected on market prices of shares and 30 stocks BSE Sensitive Index for a period of 7 years ranging from April 1995 to March 2002. Six holding periods of one year (1995-96), two years (1995-97), three years (1995-98), four years (1995-99), five years (1995-2000) and six years (1995-2001) were considered to calculate returns and variances-covariances of securities for constructing portfolios using Makowitz approach. Three levels of expected annual returns viz. 15, 20 and 25 percent were taken to construct the optimal portfolios. Fifty-four portfolios were constructed with three samples of securities, six holding periods and three levels of expected return using Markowitz Mean - Variance Model. Twenty-three portfolios were also constructed with the same data using the Sharpe’s Single Index Model. The constructed portfolios were evaluated using well-established risk adjusted performance measures of Sharpe, Treynor, Jenson and Fama, during one year immediately following their formation. It was concluded that Markowitz’s model is certainly a better approach in reducing portfolio risk as the portfolios formed using this approach differ significantly in terms of risk from the portfolio formed using Sharpe’s approach. In terms of other parameters of portfolio performance, there is no significant difference between the two approaches.